Sensor Less BLDC Drive System for Conveyor Applications - T., Akash; A., Balachandar; M., Harither; M., Madan; S., Thulasi Raman; S., Gunasekaran (Journal of Electronics and Informatics, 2025)
The research aims to design and implement a sensorless Brushless DC (BLDC) motor optimized for conveyor applications. Typically, BLDC motors rely on sensors for rotor position detection to determine the rotor's location, which can increase system complexity and maintenance costs, among other drawbacks. This research explores the application of sensorless techniques, specifically back electromotive force (back-EMF) detection, to estimate the rotor position without the need for physical sensors. The proposed system comprises a step-down transformer, a bridge rectifier, an electronic commutator, and an STM32F103C8T6 microcontroller. By integrating advanced control algorithms, this system seeks to improve the efficiency, reliability, and cost-effectiveness of conveyor operations. The designed hardware for the sensorless BLDC drive system will be tested and verified for its robustness under various load conditions, demonstrating its potential applicability in industrial conveyor systems.
Keywords: BLDC motor; STM Microcontroller; Electronic commutator; Back EMF